PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN MENGGUNAKAN APLIKASI KAHOOT PADA MATERI BAGIAN TUBUH TUMBUHAN - Nur'Aini Kamilah; Sandi Budiana; Nita Karmila (STKIP Subang, 2026)
This study aims to create an interactive learning evaluation instrument using the Kahoot application that can improve students’ learning outcomes. The research was conducted at SDN Pengasinan 2, Bekasi City, involving 33 fourth-grade students during the first semester of the 2024/2025 academic year. The validity test was carried out by six experts, consisting of two media experts, two language experts, and two material experts. In addition to expert assessments, a student response questionnaire was also distributed. The validation results show that the media experts gave scores of 96% and 98%, while the language experts also provided scores of 96% and 98%. The material experts, consisting of a lecturer and a teacher, assessed the instrument at 87% and 89%, indicating that the instrument was highly feasible for use. Student response questionnaires obtained an average score of 90.48%, showing a very positive response to the use of the instrument. Item analysis revealed that out of 20 questions, 17 were valid and 3 were invalid. The reliability test produced coefficients of 0.55 for the pre-test and 0.75 for the post-test, which fall into the moderate to high categories. The difficulty level analysis shows that pre-test items were dominated by the moderate category, while post-test items were mostly in the easy category. The effectiveness of the instrument is evident from the increase in the average score from 55.45 pre-test to 83.49 post-test, with an N-gain of 0.65, classified as moderate.